2021
DOI: 10.1186/s10020-021-00331-1
|View full text |Cite
|
Sign up to set email alerts
|

Liquid biopsy as an option for predictive testing and prognosis in patients with lung cancer

Abstract: Background The aim of this study was to investigate the clinical value of liquid biopsy as a primary source for variant analysis in lung cancer. In addition, we sought to characterize liquid biopsy variants and to correlate mutational load to clinical data. Methods Circulating cell-free DNA was extracted from plasma from patients with lung cancer (n = 60) and controls with benign lung disease (n = 16). Variant analysis was performed using the AVENI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 66 publications
(66 reference statements)
0
9
0
Order By: Relevance
“…For example, Oncomine Comprehensive Assay by Thermo Fisher and The TruSight Oncology 500 assay by Illumina are hybrid panels including all three NTRK genes ( 56 , 57 ). Currently, a number of NGS panels based on DNA or RNA are designed for liquid biopsy when no sufficient tumor tissue specimen is available, such as Guardant360 panel ( 58 ) and AVENIO Extended ctDNA Analysis Kits ( 59 ). However, the sensitivity of such methods still requires future improvement.…”
Section: Diagnosis Of Ntrk Fusionsmentioning
confidence: 99%
“…For example, Oncomine Comprehensive Assay by Thermo Fisher and The TruSight Oncology 500 assay by Illumina are hybrid panels including all three NTRK genes ( 56 , 57 ). Currently, a number of NGS panels based on DNA or RNA are designed for liquid biopsy when no sufficient tumor tissue specimen is available, such as Guardant360 panel ( 58 ) and AVENIO Extended ctDNA Analysis Kits ( 59 ). However, the sensitivity of such methods still requires future improvement.…”
Section: Diagnosis Of Ntrk Fusionsmentioning
confidence: 99%
“…Literature search generated 517 papers: after reading the titles, abstracts and full-text, 17 articles were included in the meta-analysis ( Rachiglio et al, 2016 ; He et al, 2017 ; Yang et al, 2017 ; Guo et al, 2018 ; Ito K et al, 2018 ; Wan et al, 2018 ; Ding et al, 2019 ; Li et al, 2019 ; Papadopoulou et al, 2019 ; Schrock et al, 2019 ; Lin et al, 2021 ; Park et al, 2021 ; Qvick et al, 2021 ; Satapathy et al, 2021 ; Batra et al, 2022 ; Ito M et al, 2022 ; Prabhash et al, 2022 ), summing up to a total of 1711 patients. Figure 1 represents the flowchart of the selection process, following PRISMA guidelines [PRISMA ( prisma-statement.org )].…”
Section: Resultsmentioning
confidence: 99%
“…AVENIO ctDNA Surveillance kit (Roche) is also a commercial panel using hybridization-based target enrichment. A study using AVENIO ctDNA Surveillance kit showed sensitivity of 72.73%, specificity of 100%, and concordance rate of 94.23% ( 41 ).…”
Section: Resultsmentioning
confidence: 99%